Anxiety factors in students in completing thesis - Yulanda Prabawati, Aliffia; Ratna Estria, Suci (Proceedings Series on Health & Medical Sciences, 2020)
Thesis is one part of a subject that is considered difficult by students, the difficulties and obstacles develop into negative attitudes that can eventually cause anxiety which also causes students to delay the preparation of their thesis. The anxiety felt by students can be reduced by the support of their families, especially parents. The purpose of the study is to describe the anxiety factor in students in completing thesis in University of Muhammadiyah Purwokerto. The research design used is descriptive qualitative with a phenomenological approach. This research method is a method of observation and interviews with 6 participants. Qualitative data collection was conducted at the Faculty of Health Sciences (FIKES) at University of Muhammadiyah Purwokerto in February-April 2020. To make it easier to find some keywords to obtain the theme to be discussed, it uses the MAXQDA 2018 software in this study. The anxiety factor of the participants was strongly influenced by the role of the family, especially the parents, towards attitudes and personalities of individuals in completing the thesis. And based on the results of research regarding the anxiety factor from participants, it can be concluded that it was strongly influenced by the role of the family, especially the parents, towards attitudes and personalities of individuals in completing the thesis.